PEER ASSOCIATION AT SMP N 32 SOLOK AMBAH SIJUNJUNG DISTRICT - _, Nuraiman; Sari, Nila; _, Fauziah (Jurnal Ilmu Pendidikan Ahlussunnah, 2023)
This research is motivated by the association of students of SMP N 32 Solok ambah in Sijunjung district. The aim of the researcher was to describe the association of peers at SMP N 32 Solok Ambah, Sijunjung Regency. Factors that influence peer interaction at SMP N 32 are the influence of children with their peers in the outside environment, such as playing on mobile phones with indefinite time, dating freely and smoking. The impact of peer interaction on children in the community.